Pengembangan Materi Ajar Keragaman Suku Bangsa di Sulawesi Selatan pada Siswa Kelas IV SD - Nur Hamida Hawir Rampean; Hisbullah Hisbullah (IAIN Palopo, 2021)
This study aims to determine the needs, design, and validity of teaching materials in the form of teaching material for the diversity of ethnic groups in South Sulawesi for the fourth grade students that have been developed. Based on the results of observations made by researchers that grade IV students in the material of ethnic diversity in Indonesia, students need a concrete (real) learning in the form of an interesting textbook. This research is a type of Research and Development (R&D) research using a 4-D research model consisting of four stages, namely 1) the devine stage consisting of initial condition analysis, student analysis, material analysis, and learning objectives analysis 2) design stages or designing a product 3) the development stage or product development 4) the dessiminate stage or dissemination. The subjects of this study were students of class IVB consisting of 25 students. This research data collection method in the form of teacher and student questionnaire instruments, interviews, tests, observations and validation sheets. Based on the results of the validity of the linguists, and the design of the content of the teaching materials received an assessment in the range of 0.78-100 and the pre-activation of teaching materials was in the range of values from 0.89 to 1.00, which means it was categorized as valid and very valid.